Osteodystrophy Fibrosa in a Juvenile Goat - Ravi Dabas; Siraj Ansari; Pratyanshu Srivastava; Vinita Rajpurohit; Bhupender; Yogesh Soni (Disease and Health: Research Developments Vol. 1, 2024)
Osteodystrophy is a broad term used to encompass conditions where bones either fail to develop normally or experience abnormal metabolism despite being mature. Fibrous osteodystrophy is also called osteitis cystic fibrosa. Fibrous osteodystrophy is a metabolic disease in goats characterized by bone resorption due to prolonged hypersecretion of parathyroid hormone, often caused by diets high in phosphorus or low in calcium. In this case, an 8-month-old goat kid was brought to the Referral Veterinary Polyclinic of ICAR-IVRI with a history of anorexia and noticeable bilateral facial swelling. Upon further inquiry, it was found that the owner had been regularly feeding the kid a diet primarily consisting of wheat bran and barley. Clinical examination revealed the goat kid to be dull and depressed, though its rectal temperature remained within the normal range. Hematobiochemical analysis showed decreased serum calcium levels (7 mg/dl) and elevated maleate (AvilTM, 1 ml for 5 days), oral syrup CalcimustTM (5 ml for 5 days), intravenous injection of Calcium SandozTM (10 ml in 200 ml normal saline solution), and a single dose of anabolic steroid Nandrolone (50 mg). The owner was also advised to discontinue feeding wheat bran and barley immediately. It was concluded that timely diagnosis through hematobiochemical analysis and radiographic imaging, combined with appropriate therapeutic interventions including calcium supplementation, anabolic steroids, and dietary adjustments, resulted in a favourable outcome with complete recovery within 14 days. The kid began to show improvement after 5 days, with a full recovery observed 14 days post-treatment.